PERSEPSI PEREMPUAN BATAK TOBA TERHADAP PEMBAGIAN WARISAN PADA MASYARAKAT BATAK TOBA DI KECAMATAN SIBORONGBORONG KABUPATEN TAPANULI UTARA - Suharyati L Lumbantoruan; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: The diverse customary laws still apply to Indonesian ethnic groups. Indigenous peoples in Indonesia are divided into three groups, namely: Patrineal family structure, Matrineal family, and Parental family. Inheritance, patrineal law still distinguishes gender, one of them is the division of inheritance in Batak Toba society. The purpose of this research is (1) To know the structure of kinship and the procedure of dividing inheritance in Toba Batak society (2) To know the position of girls in the division of Toba Batak's inheritance (3) To know Batak Toba community in relation of perception of Toba Batak women to the division inheritance in Batak Toba society. The research benefits are Giving a thought discipline of science especially sociology, anthropology, and law of inheritance, who want to study aspects of culture in customary order that integrates society through the division of inheritance. This research is also expected to increase the knowledge of traditional figures, the community and the world of academia and government, related to the perception and position of girls in obtaining the inheritance in Batak Toba society. The results showed that the Toba Batak kinship structure in Kecamatan Siborongborong still following patrineal kinship system. Assuming that girls do not accept that they do not get the inheritance of their parents, but at this moment the position of boys and girls together has been entitled / part of the estate of his parents. Included also in terms of getting the education has got the same rights. The Batak Toba community in Siborongborong sub-district has included girls as heirs, according to the agreement of parents and heirs.Keywords: Girls, Inheritance, Batak Toba